FUNCTIONAL ANALYSIS OF TEXTS OF OFFICIAL DOCUMENTS IN ENGLISH, UZBEK AND RUSSIAN LANGUAGES - Saidova Mamura Suleymanovna; Abdurakhmanova Aliya Yakubovna (Journal of new century innovations, 2024)
Annotation: This paper presents a comparative functional analysis of official documents in English, Uzbek and Russian languages. Official documents serve as crucial means of communication in governmental, legal, and administrative domains, conveying information, issuing instructions, and enacting policies. Understanding the linguistic features and functions of such texts is essential for effective communication and intercultural understanding.